Subcutaneous immunoglobulin replacement therapy in the treatment of patients with primary immunodeficiency disease - Suzanne Skoda-Smith; Troy R Torgerson; Hans D Ochs (Dove Medical Press, 2009)
Suzanne Skoda-Smith, Troy R Torgerson, Hans D OchsSeattle Children’s Research Institute and Department of Pediatrics, University of Washington, Seattle, WashingtonAbstract: Antibody deficiency is the most frequently encountered primary immunodeficiency disease (PIDD) and patients who lack the ability to make functional immunoglobulin require life-long replacement therapy to prevent serious bacterial infections. Human serum immunoglobulin manufactured from pools of donated plasma can be administered intramuscularly, intravenously or subcutaneously. With the advent of well-tolerated preparations of intravenous immunoglobulin (IVIg) in the 1980s, the suboptimal painful intramuscular route of administration is no longer used. However, some patients continued to experience unacceptable adverse reactions to the intravenous preparations, and for others, vascular access remained problematic. Subcutaneously administered immunoglobulin (SCIg) provided an alternative delivery method to patients experiencing difficulties with IVIg. By 2006, immunoglobulin preparations designed exclusively for subcutaneous administration became available. They are therapeutically equivalent to intravenous preparations and offer patients the additional flexibility for the self-administration of their product at home. SCIg as replacement therapy for patients with primary antibody deficiencies is a safe and efficacious method to prevent serious bacterial infections, while maximizing patient satisfaction and improving quality of life.Keywords: subcutaneous immunoglobulin, primary immunodeficiency disease, antibody deficiency, X-linked agammaglobulinemia, common variable immune deficiency